Prevalence of Hepatitis B and Hepatitis C Virus Infections and Their Co-infections Among Patients on Maintenance Haemodialysis: A Cross- Sectional Study from a Rural Tertiary Care Centre of South Bihar - Kumar, Rakesh; Vardhan, Harsh; Kumar, Ashwini; Barnwal, Ravindra Kumar; Ranjan, Sonali (Journal of Neonatal Surgery, 2025)
Background: Patients undergoing maintenance haemodialysis are at increased risk for transfusion-transmitted infections (TTIs), particularly Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV), due to frequent vascular access, transfusions, and potential lapses in infection control practices. Co-infections with HBV and HCV further complicate patient outcomes and increase the burden on healthcare systems, especially in rural regions. Objectives: This study aimed to determine the prevalence of HBV, HCV, and their co-infection among patients on maintenance haemodialysis. Specific objectives included estimating the individual prevalence of HBV and HCV, identifying co-infection rates, and analyzing associated risk factors. Methods: A hospital-based cross-sectional study was conducted at the dialysis unit and Microbiology Laboratory of Narayan Medical College & Hospital, Sasaram, from January 2023 to July 2024. A total of 208 patients undergoing maintenance haemodialysis were included. Serological testing for HBsAg and anti-HCV antibodies was performed using ELISA-based ErbaLisa kits. Data on demographic profiles, dialysis duration, and infection status were analyzed using descriptive statistics and comparative methods. Results: Among the 208 patients, 134 were males and 74 females. The prevalence of HBV (HBsAg reactive) was 2.9% (6 patients), while HCV (anti-HCV reactive) was found in 13.5% (28 patients). Co-infection (both HBV and HCV reactive) was observed in 1.0% (2 patients). HCV prevalence was notably higher among patients with longer dialysis durations. Males showed slightly higher infection rates than females, though the difference was not statistically significant. Conclusion: The study highlights the continued risk of HBV and HCV among haemodialysis patients, especially in rural settings. Enhanced infection control measures, regular screening, and strict adherence to universal precautions are essential to mitigate the spread of these infections.